Stimulation of bilirubin catabolism in jaundiced Gunn rats by an inducer of microsomal mixed-function monooxygenases - Kapitulnik, Jaime (1978)
The homozygous, jaundiced Gunn rat compensates for its inability to form bilirubin conjugates by production of polar bilirubin metabolites which can be excreted in the bile without conjugation. To assess whether microsomal mixed-function monooxygenases might be involved in formation of these metabolites, a potent inducer of these enzymes, 2,3,7,8-tetrachlorodibenzo-p-dioxin, was administered to Gunn rats in a single intraperitoneal dose of 10 μg/kg. Four to 6 days after treatment, plasma bilirubin levels had declined by a mean of 61%, whereas no significant change was observed in control Gunn rats that received only the dioxane vehicle. Use of tracer [(14)C]bilirubin showed that the decline in plasma bilirubin was the result of a 7-fold increase in fractional bilirubin turnover which reduced the bilirubin pool to an average of 11% of the control values. In the new steady state, total bilirubin turnover was unaltered. The accelerated fractional bilirubin turnover was associated with augmented biliary excretion of polar bilirubin metabolites and a 16-fold increase in hepatic benzo[a]-pyrene hydroxylase activity. Hepatic bilirubin-UDPglucuronate transferase was not induced, and no bilirubin conjugates appeared in the bile. This chemical simulation of the alternate pathways of bilirubin catabolism by the inducer suggests that microsomal cytochrome P(448)-dependent monooxygenases may be involved in the formation of the polar bilirubin metabolites excreted by the Gunn rat.